Analisis Peluang dan Ancaman Perdagangan Bahan Pangan serta Kebijakan untuk Mengatasinya: Studi Kasus Indonesia dan Thailand - Wulandari, Wulandari; Ibrahim, Shandy Akmal; Setia, M Abdika; Daspar, Daspar (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2024)
This research examines the potential for Indonesian agricultural exports to Thailand in the context of ASEAN trade. The analysis focuses on the comparative advantages of the two countries in key agricultural commodities such as rice, corn, sugar, palm oil and coffee. Production and export data for 2022 shows that Indonesia is ahead in palm oil and coffee production, while Thailand is dominant in rice and sugar exports. The 2021-2023 trade balance of both countries shows a deficit, with Thailand experiencing a much larger deficit. Despite facing challenges such as price fluctuations, climate and trade regulations, Indonesia has the opportunity to increase its agricultural exports to Thailand by improving production efficiency and product quality.